2018
DOI: 10.1074/jbc.ra118.004716
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation inhibitors compete with palmitic acid for binding to the conjugative traffic ATPase TrwD, providing a mechanism to inhibit bacterial conjugation

Abstract: Bacterial conjugation is a key mechanism by which bacteria acquire antibiotic resistance. Therefore, conjugation inhibitors (COINs) are promising compounds in the fight against the spread of antibiotic resistance genes among bacteria. Unsaturated fatty acids (uFAs) and alkynoic fatty acid derivatives, such as 2-hexadecanoic acid (2-HDA), have been reported previously as being effective COINs. The traffic ATPase TrwD, a VirB11 homolog in plasmid R388, is the molecular target of these compounds, which likely aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The docking predictions also reported the same binding site for palmitic acid. Further studies (García-Cazorla et al, 2018) have shown that the fatty acids abovementioned as TrwD inhibitors, as well as a novel inhibitor, 2-bromopalmitic acid (2-BP, Table 2), can be incorporated to the bacterial membrane and affect TrwD binding upon competition with palmitic acid. Docking studies for 2-BP showed the same binding site than that for linoleic, oleic and palmitic acid, but with a different binding mode.…”
Section: -Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…The docking predictions also reported the same binding site for palmitic acid. Further studies (García-Cazorla et al, 2018) have shown that the fatty acids abovementioned as TrwD inhibitors, as well as a novel inhibitor, 2-bromopalmitic acid (2-BP, Table 2), can be incorporated to the bacterial membrane and affect TrwD binding upon competition with palmitic acid. Docking studies for 2-BP showed the same binding site than that for linoleic, oleic and palmitic acid, but with a different binding mode.…”
Section: -Bpmentioning
confidence: 99%
“…Similarly, tanzawaic acids have potential as conjugation inhibitors ( Getino et al, 2016 ). In particular, TrwD R 388 , the VirB11 analog of R388 plasmid, has been the target of the abovementioned fatty acids and some derivatives, such as 2-bromopalmitic acid ( Ripoll-Rozada et al, 2016 ; García-Cazorla et al, 2018 ).…”
Section: Inhibition Of T4cps To Control Antibiotic Resistance Dissemimentioning
confidence: 99%
“…This "cleaved complex" is characterized by the presence of DNA breaks, which have been crystallized and found to have the fluoroquinolone C-7 ring system facing the GyrB subunit (Mustaev et al, 2014). In the case of 1, it was demonstrated that this compound displayed COIN activity in E. coli by the inhibition of TrwD ATPase (Garcia-Cazorla et al, 2018;Getino et al, 2015;Ripoll-Rozada et al, 2016). It was shown that 1 binds to the N-terminal domain (NTD) and the linker region of TrwD ATPase resulting in the restriction of the movement of the NTD over the catalytic domain (CTD), which would result in a reduction of the TrwD ATPase activity (Ripoll-Rozada et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Ripoll‐Rozada and collaborators, they identified that TrwD, a Type IV secretion traffic ATPase, is involved in the 1 ‐mediated conjugation inhibition. Moreover, 1 , which is also a potent COIN, displayed powerful inhibitory ATPase activity of TrwD as well, demonstrating that TrwD is the molecular target of 1 (Garcia‐Cazorla et al, ; Ripoll‐Rozada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the proteins integrating the T4SS, there is one ATPase, generally termed VirB11, which seems to be the target of these uFAs [18]. The protein is able to bind palmitic acid one of the major components of the bacterial membrane; but the uFAs can replace palmitic acid and reduce the ATPase activity of VirB11, hindering conjugation [19]. Thus, it seems that a promising avenue to reduce the flux of AMR genes by HGT is becoming available, although so far this approach is limited in the number of plasmids and the bacteria assayed.…”
Section: Strategies To Tackle Transmission Of Amrmentioning
confidence: 99%